From Stone Age to Stellenbosch : Studies on the Ancient Near East in Honour of Izak (Sakkie) Cornelius - Cornelius, Izak, 1958-; Dijk-Coombes, Renate M. van.; Swanepoel, Liani C.; Kotzé, Gideon R. (Münster : Zaphon Verlag, 2021)
The Old Testament scholar Izak (Sakkie) Cornelius has devoted his ongoing scholarly career to the cultures of the ancient Near East (including North Africa and Western Asia). In accordance with a focal point of his scientific research several of the studies assembled in this festschrift are devoted to the images of the divine and to that of goddesses in particular, encompassing the antiquities of Israel/Palestine, Egypt and the Near East.
From stone age to Stellenbosch : an introduction to the volume / Renate M. van Dijk-Coombes, Liani C. Swanepoel, Gideon R. Kotzé -- Were goddesses already worshipped in the early chalcolithic period? / Silvia Schroer -- A great cat walks south : a petroglyph from Kharga Oasis (Egypt) / Salima Schroer -- The many faces of Enheduanna's Inana : literary images of Inana and the visual culture from the Akkadian to the Old Babylonian period / Renate M. van Dijk-Coombes -- She walks in beauty : an iconographical study of the goddess in a Nimbus / Takayoshi M Oshima, Alison Acker Gruseke -- The many faces of the goddess : Sekhmet / Christian Frevel -- Another face of the goddess : a terracotta plaque from Qubur al-Walaydah / Angelika Berlejung -- Frauenbildnisse und ihre Gesten / Astrid Nunn -- Feeding, nursing, caring ... : some notes on the woman and child figurines from Persian period Israel/Palestine / Katharina Pyschny -- A conflation of divine and royal imagery? The case of the winged symbol in Achaemenid Persia / Louis C. Jonker -- Die Beterstatue von Tell Fekheriye als Dokument der Königsideologie des Herrschers Haddayis'i von Bit Bahiani / Herbert Niehr -- Yahweh and his Asherah in the three Pithoi inscriptions from Kuntillet ʻAjrud : a re-evaluation / Martin Leuenberger -- The horizontal dimension of the ancient and biblical view of the world / Izaak J. de Hulster -- Looking again at the nakedness of Noah / Gideon R. Kotzé -- Clapping and shouting in Psalm 47:2 with attention to the iconography of applause / Joel M. LeMon -- Fake, pseudo or true? Classifying two votive animal mummies from a South African museum / Ruhan Slabbert, Liani C. Swanepoel -- South Africa and the ancient world : artefacts and their use in teaching and outreach / Samantha Masters, Franziska Naether -- Index of ancient sources
Includes bibliographical references and index
14 English, 2 German contributions.
JSTOR
Keywords: Art, Middle Eastern; Art, Ancient -- Middle East; Goddesses -- Middle East; Goddesses in art; Art moyen-oriental.; Déesses dans l'art.; HISTORY / Ancient / General; Art, Ancient; Art, Middle Eastern; Goddesses; Goddesses in art; Middle East; Festschriften; Festschriften